1907
DOI: 10.1039/ct9079100324
|View full text |Cite
|
Sign up to set email alerts
|

XXXVI.—A reaction of certain colouring matters of the oxazine series

Abstract: BIATI'ERS OF THE OXAZINE SERIES. * The method of nuinbering is that recommended by Kehrmaiin and Gaulie (Ber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1946
1946
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…This observation suggests that an irreversible transformation of either 1 or 1‐H + is taking place in parallel, an hypothesis confirmed by spectrum F that was obtained after one day at 20 °C and exhibits a further drop in absorbance. Previous authors had indicated that Nile Blue A in its acidic form ( 1‐H + ) is not stable hydrolytically and reacts with traces of water in organic solvents to yield Nile Red 2 according to the overall reaction depicted in Scheme (hydrolysis of the reactive iminium salt 1‐H + obtained after protonation of the imine functional group in 1 ) . The observed spectral evolution appears indeed compatible with such an observation and a significant contamination by 2 (λ max at 525 nm in benzene) over time.…”
Section: Resultssupporting
confidence: 61%
“…This observation suggests that an irreversible transformation of either 1 or 1‐H + is taking place in parallel, an hypothesis confirmed by spectrum F that was obtained after one day at 20 °C and exhibits a further drop in absorbance. Previous authors had indicated that Nile Blue A in its acidic form ( 1‐H + ) is not stable hydrolytically and reacts with traces of water in organic solvents to yield Nile Red 2 according to the overall reaction depicted in Scheme (hydrolysis of the reactive iminium salt 1‐H + obtained after protonation of the imine functional group in 1 ) . The observed spectral evolution appears indeed compatible with such an observation and a significant contamination by 2 (λ max at 525 nm in benzene) over time.…”
Section: Resultssupporting
confidence: 61%
“…Nile Red was prepared according to Thorpe 21 and was purified by column chromatography over silica‐gel 60 (Merck), using ethanol as eluent. After drying, the final product was 16% yield and 99.4% purity [determined by high‐performance liquid chromatography (HPLC)].…”
Section: Experimental and Methodsmentioning
confidence: 99%
“…Nile red is a component of the commercially prepared, nonfluorochome, lipid stain Nile blue (Conn 1961), which has been used as a histochemical stain for lipids since 1908 (Smith 1908;Cain 1947;Dunnigan 1968;Fowler and Greenspan 1985;Greenspan et al 1985;Knight et al 2002). This Nile blue (phenoxazine dye) can be converted to phenoxazones (nonionic red or yellow compounds) by boiling in dilute sulphuric acid (Thorpe 1907). According to Smith (1908), Nile blue itself can either bind to fatty acids, or the Nile red component can partition into the lipids.…”
Section: Nile Red As a Fluorochrome To Detect Suberin Lamellaementioning
confidence: 99%